The Opposition in Peruvian Political Transition between years 2000 and 2002 - Hermoza Alarcón, Gustavo (2018)
The present research’s topic is how was the political parties’s participation during the end of Fujimorismo. It is specially analyzed partie’s constitution, identifying leaders and their political ideology. Another relevant section of the research is about the relations with their social bases, explaining their weaknesses and strenghts in dealing with this issue. First, parties that emerged after 2000 are characterized by an structure lacking of institucional bases. Their leaders arises from improvisation, as a result of the party system collapse in the eighties. It is also remarked the influence of the Peruvian Army in local politics. In this context, technocracy becomes the most important institucional reference, aside with new political ideologies that compete in the electoral arena